Iban gawai rituals in their twilight in Kapit, Malaysia. Issue 135 (4th May 2018) - Hasegawa, Goro
ABSTRACT: This article contributes an ethnographic on-the-ground perspective of gawai rituals in their crucial twilight phase among the Iban in the Kapit district of Sarawak, Malaysian Borneo. It reveals the processes and actors involved in these ceremonies in Iban communities in Kapit. It explores the reasons for the decline in frequency of these events, and identifies cost, migration and a loss of expertise as the main contributors to this trend. A rich and detailed perspective was gathered through accompanying a lemambang (Iban religious leader), when he officiated at these rituals. This access was enormously important for revealing the subtleties of the various rituals and allowed for the understanding of the active and inactive components of the gawai to be revealed and explored. This contribution is theoretically and practically relevant because it updates the perspective of the 1970s when gawai culture was flourishing in Iban rural life, and further explains the categories of the gawai in a fresh and expanded light. By exploring what was regarded as a disappearing culture, this article captures the continuing practice of these rituals and their significance in the social life of the Iban.